Simulation of plastic injection moulding of motorcycle fork cover using Moldex software and the Taguchi method - 323649 Mohd. Amin Rusli; Hamidon Musa, supervisor; Fakulti Kejuruteraan Mekanikal (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007